INFERTILITY AND SEXUAL DYSFUNCTIONS: A SYSTEMATIC LITERATURE REVIEW - Starc, Andrej (Acta Clin Croat, 2019)
This study aimed to investigate whether infertility and its treatment affect couple sexuality. A systematic literature review was performed, focusing on female and male sexual dysfunctions due to infertility. The method was descriptive, using a meta-synthesis of scientific research published between 2012 and 2017 in the English language. The search for suitable studies was carried out with the research databases Medline, CINAHL, PubMed and ScienceDirect using the following keywords: infertility, sexual dysfunctions, couple. It can be concluded that infertility negatively affects the sexuality of an infertile couple, which is further proven by a high percentage of sexual dysfunctions (43%-90% among women and 48%-58% among men). Couples report less satisfaction with sexuality. Since lower satisfaction and dysfunctions are closely connected with infertility and its treatment, couples might benefit from sexual therapy and support during the process of infertility treatment. Further research should focus on the evaluation of different psychological interventions that would address sexuality in couples when diagnosed and treated for infertility.